Extracting meaningful geological and structural features from 1D AEM inversions in conductive terrains. Issue 1 (2nd January 2022) - Banaszczyk, Sasha; Annetts, David; Dentith, Mike; Aitken, Alan
Abstract : Airborne electromagnetic (AEM) survey data are typically inverted with one-dimensional (1D) AEM algorithms because 1D approaches are efficient methods for calculating subsurface conductivity and thickness variations. However, 1D AEM inversion algorithms are known to perform poorly in regions where the geology is 2D or 3D. In 2013, a regional-scale (5 km spaced) TEMPEST AEM survey was acquired across the regolith dominated sedimentary and volcano-sedimentary basin terrain of the Capricorn Orogen in Western Australia. In this contribution, we evaluate the efficacy of 1D inversions of this data to map the resistivity and thickness variations of the basin geology. The limitations of 1D inversions of the Capricorn Orogen AEM data were investigated through the synthetic forward modelling and inversion of two different geological examples: (1) the depth of detection and resolution of a (1 Ωm) conductor beneath conductive regolith, and (2) the geometry resolution of a dipping contact comparing both conductor-over-resistor and resistor-over-conductor scenarios. The main findings from this study are: (1) that 1D AEM inversions reliably resolve the depth of a conductor beneath conductive cover where it is located at approximately 100–150 m below cover, and (2) that dipping layers with a strike perpendicular to an AEM survey line can be accurately recovered when their apparent dip angle is less than 20°. These results are used to interpret the resistivity and thickness variations resolved along a 1D GA-LEI TEMPEST AEM inversion from the north-eastern Yerrida Basin of the Capricorn Orogen to show that there are limitations to the level of detail which can be interpreted from 1D AEM inversions, and that there are implications for interpreters using AEM methods to map sedimentary basin sequences and structure in deeply weathered terrains.